Evaluación electrofisiológica del sistema auditivo y vestibular - Olmedo G., Diego; Chiti-Morales, Alessandra; Córdova J., Héctor; Delano, Paul H. (Revista Hospital Clínico Universidad de Chile, 2016)
The clinical evaluation of hearing loss in adult patients is usually performed by perceptual assessment through audiometer tests. This evaluation requires cooperation of the evaluated subjects. On the other hand, it is not possible to perform a perceptual audiometer test in newborns, and due to the need of an early audiological management of deafness in newborns -with hearing aids or cochlear implants-, modern medicine requires early diagnosis of hearing loss, preferably before the age of three months. Several electrophysiological clinical tools have been developed in audiology that allow us to make early diagnosis of hearing loss in those who are unable to respond an audiometry. The electrophysiological evaluation of the auditory system includes cochlear potentials, auditory brainstem responses, and cortical auditory evoked potentials. On the other hand, the electrophysiological evaluation of the vestibular system includes the cervical and ocular myogenic vestibular potentials (cVEMPs and oVEMPs). This article also includes a brief description of otoacoustic emissions, which are not an electric measure of the central nervous system, but are widely used as a diagnostic tool in pediatric audiology. The physiological advances in the knowledge of the auditory system allowed the early diagnosis of hearing loss in the newborn. However, none of these electrophysiological tests replaces the perceptual evaluation of hearing thresholds with audiometric tests.